Design of Offset Type Redundant Globoidal Cam - Shi Difen; Cao Jujiang; Liang Jinsheng; Zhang Chaoyang (Jixie chuandong)
In the actual manufacturing process of globoidal cam,due to the processing surface of globoidal cam is always considered as symmetrical structure,hence the interference between the tool and the workpiece is easy to be formed. Aiming at the processing problem,the design theory of offset type redundant globoidal cam is proposed. Through the double cannelure,the redundant drive surface is designed,the loading capacity of globoidal cam is improved. By using the MATLAB and UGNX software,the precise calculation,modeling of the offset type redundant globoidal cam are carried out.